(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2019)
PERTAMINA (Persero) RU III Plaju-Sungai Gerong is a processing unit owned by PT. PERTAMINA. One of the units found at PT. PERTAMINA RU III Plaju, a unit of Residue Fluid Catalytic Cracking Unit (RFCCU), which is located in the Crude Distiller and Light Ends (CD & L) section, which is part of the processing and production of petroleum. Reliability of operation on the Reactor and Regenerator at the RFCCU is one of the determining factors for further processes in the next unit. This study aims to determine the operating conditions of Reactors and Regenerators that are good in order to achieve the desired product and know about the problems found in the Reactor and Regenerator. Based on reactor temperature specification data, which is 515-590ᵒC and the reactor pressure specifications are 1.5-1.69 kg/cm2, while the regenerator temperature specifications are 676-770ᵒC and the regenerator pressure specifications are 1.4-190 kg/cm2. The temperature and pressure on the reactor and regenerator, 11-25 July 2018 are still within the internal limits of the catalytic cracking process. The average reactor temperature is 506.7ᵒC and the reactor pressure is 1.47 kg/cm2, while the temperature of the regenerator is 677ᵒC and the regenerator pressure is 1.31 kg/cm2. In this study, to get a good operating condition of the reactor and regenerator, it must be considered in the addition and withdrawal of the catalyst continuously in order to maintain the activeness of the catalyst to the feed. Keywords: Catalyst Silica Alumina; Catalytic cracking; Reactor and Regenerator.